Building Digital Identity Systems: A Systematic Literature Review of Three Countries' Approaches - Shelina Fransiosa; Laode Rudita (Dinasti Publisher, 2025)
This study aims to analyze strategies for developing national digital identity systems using a systematic literature review (SLR) approach by comparing practices in three countries: India, Estonia, and Indonesia. Eight recent scholarly articles were reviewed to identify each study's research objectives, methods, key variables, findings, and limitations. The analysis reveals that India stands out in terms of system coverage and scalability through Aadhaar, but faces serious challenges in data protection and audit mechanisms. Estonia has successfully developed a legal, secure, and publicly trusted digital identity system by integrating the GDPR and eIDAS frameworks. Meanwhile, Indonesia is in the early stages of developing its Digital Population Identity (IKD), facing various obstacles such as infrastructure disparities, low digital literacy, and suboptimal regulatory governance and inter-agency coordination. The study concludes that the development of digital identity systems depends not only on technology but also on policy integration, public participation, and institutional readiness. Strategic recommendations include strengthening data protection regulations, building inclusive digital infrastructure, enhancing human resource capacity, and formulating a national digital literacy